2014
DOI: 10.17533/udea.iee.v32n1a05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of education on quality of life of family caregivers of children with leukemia referred to the Oncology Clinic at Kerman’s Afzali-Poor Hospital (Iran), 2012

Abstract: Invest Educ Enferm. 2013;31(3) • 41 Effect of education on quality of life of family caregivers of children with leukemia referred to the Oncology Clinic at Kerman's Afzali-Poor Hospital (Iran), 2012Objective. To investigate the impact of education on the quality of life of parent of children with leukemia referred to the oncology clinic at Kerman's Afzali-Poor hospital (Iran). Methodology. This was an interventional study with 80 parents of children with leukemia; all of the caregivers were mothers and were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Having a child with cancer dramatically changes the psychological health of these mothers due to fear, anxiety, uncertainty of the future, and the social and financial changes imposed by the treatment from diagnosis to final outcome. [14][15][16][17] The use of psychosocial intervention measures has been shown to favor meeting the demands of the caregiver of the child with cancer, showing significant improvements in the group of mothers who had this type of support. 18 In the sociodemographic data and quality of life category, the relationship of the sociodemographic factors with the quality of life of mothers of children with cancer was described in four studies, punctuating situations of unemployment, larger number of children, family disorganization, and scarcity of financial resources as impediments to the access to minimum requirements and important to human dignity, translating into low scores of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Having a child with cancer dramatically changes the psychological health of these mothers due to fear, anxiety, uncertainty of the future, and the social and financial changes imposed by the treatment from diagnosis to final outcome. [14][15][16][17] The use of psychosocial intervention measures has been shown to favor meeting the demands of the caregiver of the child with cancer, showing significant improvements in the group of mothers who had this type of support. 18 In the sociodemographic data and quality of life category, the relationship of the sociodemographic factors with the quality of life of mothers of children with cancer was described in four studies, punctuating situations of unemployment, larger number of children, family disorganization, and scarcity of financial resources as impediments to the access to minimum requirements and important to human dignity, translating into low scores of quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Ghodsbin et al (2014) in Iran, the mean age of the mothers of children with ALL was 34.1-34.8 years. It was observed that the mean caregiver burden score (42.68±16.66) of the mothers in this study was moderately high while the mean life satisfaction score (13.82±7.00) was low.…”
Section: Discussionmentioning
confidence: 99%
“…All studies selected for nal analysis were published from 2014 to 2022. Four studies were published in 2019 (35,36,44,48), another four studies in 2021 (38,41,43,49), two studies in 2022 (34,40), two studies in 2018 (39,47) and one study in 2014 (37) and 2015 (42).…”
Section: 1 Study Characteristicsmentioning
confidence: 99%
“…The sixteen studies included in the review included ve studies from Iran (34)(35)(36)(37)(38), four from Sweden (39-42), three from USA (43)(44)(45) and one study each from Chile (46), China (47) and Indonesia (48). One study was conducted in both USA and Saudi Arabia (49).…”
Section: 1 Study Characteristicsmentioning
confidence: 99%